Oxidation rate of different monoglycides by potassium ferricyanide in alkaline media (Revista Española de Fisiología, 1948)
The differences in reducing power of some monoglycides on alkaline ferricyanide have been studied, finding that at 60º C and in a time of 2 hours their relative values taking that of the fructose as 100 are: glucose 15.3, arabinose 9.3, mannose 5.1, and galactose 4.2.